2018
DOI: 10.1039/c8cp00936h
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of indole upon X-ray absorption

Abstract: A photofragmentation study of gas-phase indole (C8H7N) upon single-photon ionization at a photon energy of 420 eV is presented. Indole was primarily inner-shell ionized at its nitrogen and carbon 1s orbitals. Electrons and ions were measured in coincidence by means of velocity map imaging. The angular relationship between ionic fragments is discussed along with the possibility to use the angle-resolved coincidence detection to perform experiments on molecules that are strongly oriented in their recoil-frame. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Recently, the valence band and core-level spectra of gaseous indole, 2,3-dihydro-7-azaindole, and 3-formylindole were measured by X-ray photoemission spectroscopy and interpreted by quantum-chemistry calculations . An inner-shell photoionization study of indole in the gas phase was published by Kierspel and co-authors, and detailed information about its photoionization and photofragmentation spectra upon single-photon inner-shell ionization was reported. To the best of our knowledge, complete electronic structure data recorded by X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy techniques exist only for gaseous 3-methylindole. , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the valence band and core-level spectra of gaseous indole, 2,3-dihydro-7-azaindole, and 3-formylindole were measured by X-ray photoemission spectroscopy and interpreted by quantum-chemistry calculations . An inner-shell photoionization study of indole in the gas phase was published by Kierspel and co-authors, and detailed information about its photoionization and photofragmentation spectra upon single-photon inner-shell ionization was reported. To the best of our knowledge, complete electronic structure data recorded by X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy techniques exist only for gaseous 3-methylindole. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, electrons and ions were measured in coincidence in a velocity-map-imaging mode to extract 2D and 3D velocity vectors of the charged particles. It was found that the fragmentation channels depend on the ionized electronic states, i.e., the potential energy surfaces, whereas the observed velocities of the fragments are not strongly dependent on these chemical details . However, it appears that up to now experimental evidence concerning the full valence and core electronic structure for derivatives of indole under isolated conditions is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…An inner-shell photoionization study of a gas-phase indole was published by Kierspel and co-authors. 37 Detailed photoionization and photofragmentation spectra of indole upon single-photon inner-shell ionization at a photon energy of 420 eV were recorded. This photon energy was chosen so that indole could be locally ionized at its nitrogen or carbon atoms.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst originally developed to simplify data-retrieval in ion and electron imaging experiments within the Controlled Molecule Imaging group [11,12], we envision that the library will help scientific and industrial use of Timepix3 and allow for more novel applications of the hardware. While we describe a slice of the capabilities provided by the library in this introductory article, this is not comprehensive.…”
Section: Pymepix Librarymentioning
confidence: 99%